HEMATOLOGICAL AND BIOCHEMICAL ALTERATIONS ASSOCIATED WITH TOXOPLASMOSIS IN DROMEDARIES (CAMELUS DROMEDARIUS) H ABITATING IN CHOLISTAN DESERT OF BAHAWALPUR, PUNJAB, PAKISTAN - M. H. Lashari; M. T. Ghouri; M. S. Akhtar; Z. Kamran M. S. Chaudhari; M. Ayaz; A. A. Farooq; G. Sarwar (Journal of Animal and Plant Sciences, 2018)
Toxoplasmosis is an important cause of reproductive failure in animals, resulting in socio economic losses all over the world. The aims of the current study was to investigate the seroprevalance of Toxoplasma gondii in Camelus dromedarius (Dromedary camels) and also to assess the hematological and biochemical alterations associated with T. gondii infection from February, 2015 to December, 2015. Blood samples were aseptically collected and were analyzed for T. gondii prevalence by direct agglutination test kits and hematobiochemical parameters by hematology analyzer. A total of 201 camels of different age were examined from 12 flocks in different Cholistan areas of Bahawalpur. Of 201 selected camels only 36 camels found seropositive of toxoplasmosis. The overall seroprevalence of toxoplasmosis was 17.91% in camels and the prevalence was found significantly ( P<0.01) highest 31.25% in camels age group of e 13 years and lowest 10.52% in age group of 9-12 years. Camels that suffered from toxoplasmosis (n=60) were subjected to hematological and biochemical analysis and matched with clinically healthy camels as control ( n=60). The haematological analysis revealed a significant (P<0.05) reduction in the total RBC count, Hb concentration, HCT, PVC, MCH, MCHC, LYM, PLT and PDW in the affected camels. In addition, significant (P<0.05) increases in WBCs, MCV, RDW, NEUT, MPV, MXD, platelets and P-LCR were observed. The biochemical analysis revealed a highly significant reduction (P<0.05) in the sugar and AST level. Significant (P<0.05) increases in ALT, total bilirubin, blood urea, uric acid and blood cholesterol levels were detected in affected camels when compared with the controls. In conclusion, T. gondii was more common in older age group of camel; moreover toxoplasmosis greatly affected the hematobiochemical parameters of camel. world. The highest population of one-humped camels is
Keywords: Toxoplasmosis; Camels; Age; Prevalence; Hematological; Biochemical